Management of critically Ill COVID-19 patients: Exploring the potential of morphine and assessing disadvantages of acetaminophen - Seyed Mohammadreza Hashemian; Ameneh Jafari; Parviz Amri Maleh (Caspian Journal of Internal Medicine)
The use of morphine should be carefully considered and administered under the supervision of medical professionals due to the risks associated with opioids, including respiratory depression and the potential for addiction or dependency. Additionally, it could be potentially harmful in late stages of severe COVID-19, especially in the presence of septic shock. Close monitoring and dosage adjustments are necessary to ensure patient safety and optimal pain management.